Emerging Trade Politics: The Continuous Pendulum from Multilateralism to Asymmetric Trade Negotiations - Saguier, Marcelo; Tussie, Diana (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2014)
In this essay we analyze the challenges of asymmetric trade agreements at a time when Mercosur and Ecuador are opening negotiations with the European Union. How can developing countries manage the terms of integration into the global economy? How do different sets of external pressures place constraints on national development strategies? What offsetting mechanisms have emerged? We discuss the dynamics of trade negotiation processes in multilateral and bilateral fora to show to what extent they reflect and reproduce entrenched power asymmetries. Moreover, we explore the opportunities and constraints available for developing country governments to offset the unequal power structure that characterise international trade negotiation processes. It is argued that while changes in the contemporary international political economy do not override historically entrenched asymmetries, they nonetheless open up opportunities to develop new approaches of engagement in trade negotiations that can mitigate and at times even overcome power asymmetries.